Resin member, active material holding member, electrode, lead-acid battery and electric vehicle

A resin member with a polyester base and epoxy-acrylic resin mixture maintains mechanical strength and prevents active material leakage in lead-acid batteries, addressing the issue of sulfuric acid exposure.

JP7611828B2Active Publication Date: 2025-01-10ENERGYWITH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021536833
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-26
Filing Date
2020-06-22
Publication Date
2025-01-10
Estimated Expiration
2040-06-22

AI Technical Summary

Technical Problem

The mechanical strength of resin-based active material holding members in lead-acid batteries decreases when they come into contact with sulfuric acid, leading to deterioration and active material leakage, which shortens battery life.

Method used

A resin member composed of a base material containing polyester and a resin mixture of epoxy and acrylic resins, with specific mass ratios, is used to suppress the decrease in mechanical strength when exposed to sulfuric acid.

Benefits of technology

The resin member maintains mechanical strength and prevents active material leakage, ensuring a sufficient battery life by resisting the corrosive effects of sulfuric acid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611828000002
    Figure 0007611828000002
  • Figure 0007611828000003
    Figure 0007611828000003
  • Figure 0007611828000001
    Figure 0007611828000001
Patent Text Reader

Abstract

A lead storage battery 100 comprises a positive electrode 10 and a negative electrode 20, wherein the positive electrode 10 includes a tube 10a for retaining an active material, the tube 10a includes a resin member, the resin member includes a base material comprising polyester and a resin retained on the base material, the resin comprises an epoxy resin and an acrylic resin, and the content of the epoxy resin is over 0 mass% to 70 mass% or less based on the total amount of the epoxy resin and the acrylic resin.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin member, an active material holding member, an electrode, a lead-acid battery, and an electric vehicle. [Background technology]

[0002] Lead-acid batteries are widely used as secondary batteries for industrial or consumer use, and there is particularly high demand for lead-acid batteries for electric vehicles (e.g., automotive lead-acid batteries, so-called batteries) and backup lead-acid batteries for UPS (Uninterruptible Power Supply), disaster prevention (emergency) radio power sources, telephone power sources, and the like.

[0003] In a lead-acid battery, an active material holding member capable of holding (accommodating) an active material is sometimes used. For example, a lead-acid battery includes an electrode having an active material holding member, a metal core (current collector) inserted in the active material holding member, and an electrode material (electrode material containing an active material) filled between the active material holding member and the metal core (see, for example, Patent Document 1 below). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 8-203506 Summary of the Invention [Problem to be solved by the invention]

[0005] Incidentally, the electrolyte in a lead-acid battery tends to contain sulfuric acid. Therefore, when an electrode having an active material holding member is used, the active material holding member comes into contact with sulfuric acid. However, in the past, when the active material holding member contains a resin material, the mechanical strength (e.g., tensile strength) of the active material holding member may decrease when the active material holding member comes into contact with sulfuric acid. When the mechanical strength of the active material holding member decreases, the active material holding member is likely to deteriorate with charge / discharge cycles, and the active material is likely to leak from the active material holding member, etc., resulting in a decrease in battery life. Therefore, it is required that the resin member for obtaining the active material holding member is prevented from decreasing in mechanical strength when it comes into contact with sulfuric acid.

[0006] An object of one aspect of the present invention is to provide a resin member capable of suppressing a decrease in mechanical strength when contacted with sulfuric acid.Another object of the present invention is to provide an active material retention member using the resin member.Another object of the present invention is to provide an electrode having the active material retention member, a lead-acid battery including the electrode, and an electric vehicle including the lead-acid battery. [Means for solving the problem]

[0007] One aspect of the present invention provides a resin member for use in an active material holding member, the resin member comprising a substrate containing polyester and a resin held on the substrate, the resin containing an epoxy resin and an acrylic resin, and a content of the epoxy resin in the substrate is more than 0 mass % and not more than 70 mass % based on the total amount of the epoxy resin and the acrylic resin.

[0008] Such a resin member can suppress a decrease in mechanical strength (e.g., tensile strength) when the resin member is brought into contact with sulfuric acid. By obtaining an active material retention member using such a resin member, even if the active material retention member comes into contact with sulfuric acid in a lead-acid battery, a decrease in the mechanical strength of the active material retention member is suppressed, and deterioration of the active material retention member due to charge / discharge cycles is suppressed, thereby ensuring a sufficient battery life.

[0009] Another aspect of the present invention provides an active material holding member including the above-mentioned resin member.

[0010] Another aspect of the present invention provides an electrode having the above-mentioned active material holding member and an active material held by the active material holding member.

[0011] Another aspect of the present invention provides a lead-acid battery comprising a positive electrode and a negative electrode, at least one selected from the group consisting of the positive electrode and the negative electrode being the above-mentioned electrode.

[0012] Another aspect of the present invention provides an electric vehicle including the lead-acid battery described above. Effect of the Invention

[0013] According to one aspect of the present invention, it is possible to provide a resin member capable of suppressing a decrease in mechanical strength when contacted with sulfuric acid. According to another aspect of the present invention, it is possible to provide an active material retention member using the resin member. According to another aspect of the present invention, it is possible to provide an electrode having the active material retention member, a lead-acid battery including the electrode, and an electric vehicle including the lead-acid battery. [Brief description of the drawings]

[0014] [Figure 1] 1 is a schematic cross-sectional view showing a lead-acid battery according to one embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing a lead-acid battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the present invention will be described in detail. However, the present invention is not limited to the following embodiment.

[0016] Since the specific gravity varies depending on the temperature, in this specification, it is defined as the specific gravity converted at 20°C. In this specification, a numerical range indicated using "~" indicates a range including the numerical values ​​described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of a numerical range of another stage. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. "A or B" may include either A or B, or may include both. Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more types. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. The term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from other processes as long as the intended action of the process is achieved.

[0017] The resin member according to the present embodiment is a resin member used for an active material holding member. The resin member according to the present embodiment includes a base material containing polyester and a resin held on the base material, the resin containing an epoxy resin and an acrylic resin, and the content of the epoxy resin is more than 0 mass% and 70 mass% or less based on the total amount of the epoxy resin and the acrylic resin. The resin member according to the present embodiment may be in a sheet shape, a tube shape, or the like, and may be a resin sheet (a sheet-shaped resin member).

[0018] The active material holding member according to this embodiment includes the resin member according to this embodiment. The active material holding member is a member for holding the active material of a battery. The "active material" includes both the active material after chemical conversion and the raw material of the active material before chemical conversion. The active material holding member according to this embodiment may include a tubular portion (e.g., a cylindrical portion) including the resin member according to this embodiment. The tubular portion can be formed by the resin member according to this embodiment. The active material holding member can hold (contain) the active material inside the tubular portion. The active material holding member according to this embodiment may include a plurality of tubular portions.

[0019] The electrode according to the present embodiment includes the active material holding member according to the present embodiment and an active material held in the active material holding member. The lead-acid battery according to the present embodiment includes a positive electrode and a negative electrode, and at least one selected from the group consisting of the positive electrode and the negative electrode is the electrode according to the present embodiment. The lead-acid battery according to the present embodiment may include a separator disposed between the positive electrode and the negative electrode, or may not include a separator. The lead-acid battery according to the present embodiment may include an electrolyte. The electrolyte may include sulfuric acid. The lead-acid battery according to the present embodiment may be a flooded lead-acid battery, a valve-regulated lead-acid battery, or the like, and may be a sealed lead-acid battery, an open lead-acid battery, or the like.

[0020] According to this embodiment, the decrease in mechanical strength (e.g., tensile strength) when the resin member is brought into contact with sulfuric acid can be suppressed. Therefore, by obtaining an active material holding member using such a resin member, even if the active material holding member in a lead-acid battery comes into contact with sulfuric acid, the decrease in mechanical strength of the active material holding member is suppressed, and the deterioration of the active material holding member with charge / discharge cycles is suppressed, so that the battery life can be sufficiently secured. Although polyester has a characteristic of being difficult to decompose by oxygen generated from the positive electrode (oxidation resistance), it tends to be easily deteriorated by sulfuric acid. On the other hand, in this embodiment, since the resin containing the epoxy resin and the acrylic resin is held on the substrate, the decrease in mechanical strength can be suppressed while maintaining the characteristic of being difficult to decompose by oxygen generated from the positive electrode.

[0021] The polyester in the base material of the resin member according to this embodiment may be a polyalkylene terephthalate such as polyethylene terephthalate. The base material may contain a material other than polyester. Examples of the material other than polyester include polyolefin (polyethylene, polypropylene, etc.), polystyrene, polyvinyl chloride, polyvinylidene chloride, polyvinylidene fluoride, polycarbonate, etc. The base material may not contain at least one of these materials (e.g., polyolefin).

[0022] The content of polyester is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 90% by mass or more, extremely preferably 95% by mass or more, very preferably 97% by mass or more, and even more preferably 99% by mass or more, based on the total amount of resin constituting the substrate. The resin constituting the substrate may be substantially composed of polyester (substantially 100% by mass of the resin constituting the substrate is polyester).

[0023] As the substrate, a nonwoven fabric, a woven fabric, or the like can be used. The fibers in the substrate may be oriented. For example, the nonwoven fabric may have an MD direction (machine direction) in the production of the nonwoven fabric, and a CD direction (width direction) perpendicular to the MD direction. Since the fibers tend to be oriented in the MD direction, the mechanical strength in the MD direction tends to be higher than that in the CD direction. Therefore, a nonwoven fabric with high mechanical strength in the CD direction also has high mechanical strength in the direction (CD direction) where the mechanical strength is relatively low.

[0024] The substrate may be a porous body having pores. The substrate preferably has a portion having an average pore diameter in the following range. The average pore diameter of the substrate is preferably 60 μm or less, more preferably 50 μm or less, even more preferably 45 μm or less, and particularly preferably 40 μm or less, from the viewpoint of easily suppressing the outflow of the electrode material. The average pore diameter of the substrate is preferably more than 2 μm, more preferably 5 μm or more, even more preferably 10 μm or more, particularly preferably 20 μm or more, extremely preferably 30 μm or more, and very preferably 35 μm or more, from the viewpoint of easily reducing the electrical resistance of the substrate. From these viewpoints, the average pore diameter of the substrate is preferably more than 2 μm and 60 μm or less. The average pore diameter can be measured by a pore distribution measuring device (for example, AUTO PORE IV 9520, manufactured by Shimadzu Corporation).

[0025] The weight of the base material is set at 200 g / m2, which is a material that reduces the resistance of the base material. 2 Less than 150 g / m 2 Less than 130 g / m is more preferable. 2 More preferably, 110 g / m 2 The weight of the substrate is particularly preferably 70 g / m from the viewpoint of resistance to deterioration due to contact with sulfuric acid in the battery and to deterioration due to oxygen generated during charging. 2 More than 80g / m is preferable. 2 More preferably, 90 g / m 2 More preferably, 100 g / m 2 From these viewpoints, the weight per unit area of ​​the substrate is preferably 70 to 200 g / m 2 The basis weight of the substrate means the mass per unit area measured in accordance with JIS L1913.

[0026] The resin held on the substrate includes an epoxy resin and an acrylic resin. By using the epoxy resin and the acrylic resin, deterioration by sulfuric acid can be suppressed and mechanical strength can be maintained.

[0027] The acrylic resin is a resin having a structural unit derived from a monomer having a (meth)acryloyl group. The acrylic resin may be a homopolymer of one type of monomer, or a copolymer of two or more types of monomers. The content of the structural unit derived from the monomer having a (meth)acryloyl group in the acrylic resin may be 50% by mass or more, 70% by mass or more, or 90% by mass or more based on the total mass of the structural units constituting the acrylic resin. The acrylic resin may be an embodiment consisting of a structural unit derived from a monomer having a (meth)acryloyl group.

[0028] Examples of the epoxy resin include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, bisphenol F novolac type epoxy resins, stilbene type epoxy resins, triazine skeleton-containing epoxy resins, fluorene skeleton-containing epoxy resins, biphenyl type epoxy resins, xylylene type epoxy resins, biphenyl aralkyl type epoxy resins, naphthalene type epoxy resins, dicyclopentadiene type epoxy resins, alicyclic epoxy resins, diglycidyl ether compounds of polycyclic aromatics (polyfunctional phenols, anthracene, etc.), and phosphorus-containing epoxy resins obtained by introducing a phosphorus compound into these.

[0029] The content of the epoxy resin is more than 0% by mass and 70% by mass or less based on the total amount of the epoxy resin and the acrylic resin. In this case, the effect of suppressing sulfuric acid deterioration and maintaining mechanical strength is sufficiently exhibited by using the epoxy resin and the acrylic resin. The content of the epoxy resin is preferably 65% ​​by mass or less, more preferably 60% by mass or less, even more preferably 55% by mass or less, and particularly preferably 50% by mass or less, from the viewpoint of easily suppressing the decrease in mechanical strength when the resin member is contacted with sulfuric acid and from the viewpoint of easily reducing the electrical resistance value when the resin member is contacted with sulfuric acid. The content of the epoxy resin is preferably 45% by mass or less, more preferably 40% by mass or less, even more preferably 35% by mass or less, and particularly preferably 30% by mass or less, from the viewpoint of easily suppressing the decrease in mechanical strength when the resin member is contacted with sulfuric acid. The content of the epoxy resin is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and particularly preferably 20% by mass or more, from the viewpoint of easily suppressing the decrease in mechanical strength when the resin member is contacted with sulfuric acid. The content of the epoxy resin is preferably 25% by mass or more, more preferably 30% by mass or more, from the viewpoint of further suppressing the decrease in mechanical strength when the resin member is contacted with sulfuric acid, and from the viewpoint of easily reducing the electrical resistance value when the resin member is contacted with sulfuric acid. The content of the epoxy resin is preferably 35% by mass or more, more preferably 40% by mass or more, even more preferably 45% by mass or more, and particularly preferably 50% by mass or more, from the viewpoint of further reducing the electrical resistance value when the resin member is contacted with sulfuric acid. From these viewpoints, the content of the epoxy resin is preferably more than 0% by mass and 65% by mass or less, and more preferably more than 0% by mass and 40% by mass or less. The content of the epoxy resin can be confirmed, for example, by TG-DTA.

[0030] The content of the resin retained on the substrate can be measured using a TG-DTA measuring device (for example, TG8120 manufactured by Rigaku Corporation) according to the following procedure. First, the sample obtained by grinding the substrate with the resin held thereon is weighed out to about 5.0 mg and placed in a container (aluminum pan) for a thermogravimetry-differential calorimeter (TG-DTA), and its mass W1 [mg] is recorded. In the measuring device, an inert gas (helium) is passed at a flow rate of 100 ml / min. The sample is heated from room temperature (e.g., 25°C) to 100°C at a heating rate of 10°C / min, and held at 100°C for 10 minutes to remove moisture from the sample. After that, the sample is heated further to 380°C at a heating rate of 10°C / min, and held at 380°C for 20 minutes. The sample is then heated further to 500°C at a heating rate of 10°C / min, and held at 500°C for 5 minutes. The mass loss W2 [mg] of the sample during the above heating process is calculated. On the other hand, as a reference sample, the temperature of only the substrate on which no resin is held is similarly increased, and the mass loss W3 [mg] of the reference sample during this temperature increase process is calculated. The resin content is calculated as the ratio of the difference between the mass loss of the sample W2 and the mass loss of the reference sample W3 to the mass of the sample W1, i.e., (W2-W3) / W1 x 100(%).

[0031] The total amount of the epoxy resin and the acrylic resin is preferably in the following range based on the total mass of the base material. The total amount of the epoxy resin and the acrylic resin is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, particularly preferably 7% by mass or more, extremely preferably 10% by mass or more, very preferably 12% by mass or more, and even more preferably 15% by mass or more, from the viewpoint of easily suppressing a decrease in mechanical strength when the resin member is contacted with sulfuric acid. The total amount of the epoxy resin and the acrylic resin is preferably 30% by mass or less, more preferably 25% by mass or less, even more preferably 20% by mass or less, and particularly preferably 15% by mass or less, from the viewpoint of easily suppressing a decrease in mechanical strength when the resin member is contacted with sulfuric acid. From these viewpoints, the total amount of the epoxy resin and the acrylic resin is preferably 1 to 30% by mass.

[0032] The resin held on the substrate may include a resin other than the epoxy resin and the acrylic resin, such as a rosin-based resin, a terpene-based resin, a petroleum-based resin, a melamine resin, a phenolic resin, or a styrene resin.

[0033] The total amount of epoxy resin and acrylic resin is preferably in the following range based on the total mass of the resins held on the substrate. The total amount of epoxy resin and acrylic resin is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 90% by mass or more, extremely preferably 95% by mass or more, very preferably 97% by mass or more, and even more preferably 99% by mass or more. The resin held on the substrate may be substantially composed of epoxy resin and acrylic resin (substantially 100% by mass of the resin held on the substrate is epoxy resin and acrylic resin).

[0034] The resin may be held on the inner or outer surface of the substrate, or on the surfaces within the pores of the substrate (collectively referred to simply as "on the substrate"). The resin may be attached to the substrate. The resin may be held on a part of the substrate, or on the entire substrate.

[0035] The amount of resin held on the substrate of the resin member in the active material holding member of the lead-acid battery after chemical formation can be measured, for example, by the following procedure. First, the lead-acid battery after chemical formation is disassembled, and the electrodes are washed in running water for 12 hours. Next, the electrodes are dried in air at 45°C for 72 hours. Then, the active material holding member is removed from the electrode (for example, the active material holding member is removed by cutting at the boundary position between the upper link and the active material holding member, and at the boundary position between the lower link and the active material holding member). Then, the core metal and active material are removed from the active material holding member, and the amount of resin held on the substrate of the resin member is measured.

[0036] In the resin member according to this embodiment, pores having a size in the range of 0.006 to 0.1 μm as measured by mercury intrusion porosimetry may account for less than 10% by volume of the total pore volume.

[0037] In the resin member according to the present embodiment, the ratio A / B of the total pore volume A of pores having a pore diameter of 10 μm or more to the total pore volume B of pores having a pore diameter of less than 10 μm may exceed 1.40. The total pore volume can be measured using a pore distribution meter (for example, AUTO PORE IV 9520, product name, manufactured by Shimadzu Corporation). The ratio A / B can be adjusted depending on the type or amount of resin held on the substrate.

[0038] The thickness of the resin member (for example, a sheet-shaped resin member) is preferably in the following range. From the viewpoint of easily suppressing the decrease in mechanical strength when the resin member is contacted with sulfuric acid, the thickness of the resin member is preferably 0.05 mm or more, more preferably 0.1 mm or more, even more preferably 0.12 mm or more, particularly preferably 0.15 mm or more, extremely preferably 0.18 mm or more, very preferably 0.2 mm or more, and even more preferably 0.23 mm or more. From the viewpoint of easily decreasing the electrical resistance of the resin member, the thickness of the resin member is preferably 1 mm or less, more preferably 0.8 mm or less, even more preferably 0.6 mm or less, particularly preferably 0.5 mm or less, extremely preferably 0.4 mm or less, very preferably 0.3 mm or less, and even more preferably 0.25 mm or less. From these viewpoints, the thickness of the resin member is preferably 0.05 to 1 mm. The average thickness value may be used as the thickness of the resin member. The average thickness value can be measured by the method described in the examples.

[0039] The cylindrical part in the active material holding member according to this embodiment has an internal space for accommodating an active material. The cross-sectional shape perpendicular to the axial direction (longitudinal direction) of the cylindrical part may be a circle, an ellipse, a rounded rectangle, or the like. The length of the cylindrical part is, for example, 160 to 650 mm. The outer diameter of the cylindrical part is, for example, 5 to 12 mm. The inner diameter of the cylindrical part is, for example, 5 to 10 mm. The active material holding member according to this embodiment may be in an embodiment consisting of the cylindrical part, or may be in an embodiment having a part other than the cylindrical part.

[0040] The active material holding member according to the present embodiment may be configured as a group of tubes for holding an active material by arranging a plurality of (for example, 2 to 19) cylindrical portions of the active material holding member in a direction perpendicular to the axial direction of the cylindrical portion. In the group of active material holding tubes, the cylindrical portions of the plurality of active material holding members are arranged side by side. The structure in which a plurality of cylindrical portions are arranged side by side may be obtained by arranging cylindrical portions that are separate from each other side, or may be obtained by forming a plurality of through holes between opposing base materials. A connection portion such as a seam (seamed portion) may be arranged between adjacent cylindrical portions. Examples of the form of the active material holding member include a spiral type and a gauntlet type. In the spiral type, a cylindrical portion is formed by winding a resin sheet in a spiral shape. In the gauntlet type, a cylindrical portion is formed by joining (for example, sewing) opposing resin sheets to each other. In the active material holding member, the cylindrical portion may be formed by winding a resin sheet having a pair of opposing sides around the cylindrical portion in a state in which the pair of sides face the axial direction of the cylindrical portion. In the active material holding member, the cylindrical portion may be formed by winding a resin sheet in a spiral shape.

[0041] "Spiral" means that the resin sheet advances in the direction of extension of the central axis while revolving around the central axis extending in a predetermined direction. "Spiral" means that the resin sheet revolves in the same plane. For example, in the case of a spiral, the cylindrical portion extends as the resin sheet is wound, whereas in the case of a spiral, the cylindrical portion thickens as the resin sheet is wound but does not extend. The winding direction (counterclockwise or clockwise) in the case of a spiral means the direction of rotation of the resin sheet relative to the central axis. The winding direction (counterclockwise or clockwise) in the case of a spiral means the winding direction when the resin sheet is wound from the inner layer to the outer layer of the cylindrical portion. The resin sheet may be wound at least once, may be wound more than once, or may be wound multiple times.

[0042] In the case where the substrate in the active material holding member having a cylindrical portion includes a nonwoven fabric, it is preferable that the MD direction and CD direction of the nonwoven fabric are inclined with respect to the axial direction of the cylindrical portion. The inclination angle of the MD direction or CD direction with respect to the axial direction of the cylindrical portion is preferably in the following range from the viewpoint of easily suppressing the influence of mechanical strength caused by fiber orientation and thus easily ensuring a sufficient battery life. The inclination angle is preferably more than 0°, more preferably 10° or more, even more preferably 20° or more, particularly preferably 30° or more, extremely preferably 40° or more, and extremely preferably 43° or more. The inclination angle is preferably less than 90°, more preferably 80° or less, even more preferably 70° or less, particularly preferably 60° or less, extremely preferably 50° or less, and extremely preferably 47° or less. From these viewpoints, the inclination angle is preferably more than 0° and less than 90°, more preferably 10 to 80°, and even more preferably 43 to 47°. It is presumed that when the inclination angle is 45°, the influence of mechanical strength caused by fiber orientation is most easily suppressed.

[0043] The electrode according to this embodiment may have a core metal (current collector) inserted into an active material holding member (e.g., a cylindrical portion). The electrode according to this embodiment may have an active material holding member having a cylindrical portion, a core metal inserted into the cylindrical portion, and an active material filled between the cylindrical portion and the core metal. The electrode according to this embodiment may have a group of tubes for holding active material.

[0044] The core is a rod-shaped member inserted into an active material holding member (e.g., a cylindrical portion), and extends, for example, in the axial direction of the cylindrical portion at the center of the cylindrical portion. The core can be obtained, for example, by casting using pressure casting. The material constituting the core may be any conductive material, and examples of such materials include lead alloys such as lead-calcium-tin alloys and lead-antimony-arsenic alloys. The lead alloy may contain selenium, silver, bismuth, etc. The cross-sectional shape of the core perpendicular to the axial direction (longitudinal direction) may be circular, elliptical, etc. The length of the core is, for example, 160 to 650 mm. The diameter of the core is, for example, 2.0 to 4.0 mm.

[0045] The lead-acid battery according to the present embodiment may include a battery case that contains electrodes (positive and negative electrodes). The electrodes may form an electrode group. For example, in the electrode group, positive and negative electrodes are alternately arranged with a separator interposed therebetween. Silica particles may not be arranged between the positive and negative electrodes. The battery case may be filled with an electrolyte. The electrolyte may contain aluminum ions, sodium ions, lithium ions, or the like. The electrolyte may not contain silica particles.

[0046] The electrode (positive electrode or negative electrode) after chemical formation has an electrode material (positive electrode material or negative electrode material) containing an active material. The electrode (positive electrode or negative electrode) may have a current collector. The electrode material can be held by an active material holding member, a current collector, or the like. The positive electrode material is held, for example, by the active material holding member according to this embodiment. The negative electrode material may be held by either an active material holding member, a current collector, or the like.

[0047] The cathode material contains the cathode active material after chemical formation. The cathode material after chemical formation can be obtained, for example, by chemical formation of an unformed cathode material containing the raw material of the cathode active material. Methods for obtaining the cathode material after chemical formation include a method in which the raw material of the cathode active material is directly charged into an active material holding member (e.g., a cylindrical part) and then chemical formation, and a method in which a cathode material paste containing the raw material of the cathode active material is aged and dried to obtain an unformed cathode material, and then chemical formation of the unformed cathode material. Examples of the raw material of the cathode active material include lead powder and red lead. Examples of the cathode active material in the cathode material after chemical formation include lead dioxide.

[0048] The positive electrode material may further contain additives as necessary. Examples of additives for the positive electrode material include short reinforcing fibers. Examples of short reinforcing fibers include acrylic fibers, polyethylene fibers, polypropylene fibers, and polyethylene terephthalate fibers (PET fibers).

[0049] The negative electrode material contains the negative electrode active material after chemical formation. The negative electrode material after chemical formation can be obtained, for example, by chemical formation of an unformed negative electrode material containing the raw material of the negative electrode active material. The negative electrode material after chemical formation can be obtained, for example, by maturing and drying a negative electrode material paste containing the raw material of the negative electrode active material to obtain an unformed negative electrode material, and then chemically forming the unformed negative electrode material. Examples of the raw material of the negative electrode active material include lead powder. Examples of the negative electrode active material in the negative electrode material after chemical formation include porous spongy lead.

[0050] The negative electrode material may further contain additives as necessary. Examples of additives for the negative electrode material include barium sulfate, reinforcing short fibers, carbon materials (carbonaceous conductive materials), etc. As the reinforcing short fibers, the same reinforcing short fibers as those for the positive electrode material may be used.

[0051] Examples of the carbon material include carbon black, graphite, etc. Examples of the carbon black include furnace black (Ketjen Black (registered trademark) and the like), channel black, acetylene black, thermal black, etc.

[0052] The material of the separator is not particularly limited as long as it prevents electrical connection between the positive electrode and the negative electrode and allows the electrolyte to pass through. Examples of the material of the separator include microporous polyethylene, a mixture of glass fiber and synthetic resin, and the like.

[0053] The resin member, active material holding member, and electrode according to the present embodiment are preferably used in a flooded lead-acid battery (resin member, active material holding member, and electrode for flooded lead-acid battery), and the lead-acid battery according to the present embodiment is preferably a flooded lead-acid battery. In general, in a flooded lead-acid battery, the entire electrode tends to be immersed in the electrolyte, and the amount of electrolyte tends to be larger than in a valve-regulated lead-acid battery. In this case, the discharge capacity is less likely to be regulated by the amount of electrolyte, so that the discharge capacity tends to be large. However, in a flooded lead-acid battery, the concentration of sulfuric acid in the region below the electrode increases due to stratification of the electrolyte, and the resin member below the active material holding member in the electrode is likely to deteriorate. In addition, in a flooded lead-acid battery, the active material (e.g., positive electrode active material) becomes muddy as aging (including deterioration due to charge / discharge cycles) progresses, and the active material becomes prone to leak. In these cases, if the mechanical strength of the resin member is reduced when it is contacted with sulfuric acid, the active material will leak significantly. On the other hand, in the resin member according to the present embodiment, the decrease in mechanical strength of the resin member when it comes into contact with sulfuric acid can be suppressed, and therefore it is possible to utilize the advantages of a flooded lead-acid battery while suppressing leakage of active material.

[0054] An example of a lead-acid battery according to the present embodiment will be described with reference to Figs. 1 and 2. Figs. 1 and 2 are schematic cross-sectional views showing an example of a lead-acid battery. In Fig. 1, positive and negative electrodes are alternately arranged with separators interposed between them from the front side to the back side of the drawing. Fig. 1(b) is an enlarged view showing region P in Fig. 1(a). In Fig. 1(a), details of the inside of the tube and details of the portion where the tubes are adjacent to each other are omitted. The lead-acid battery shown in Figs. 1 and 2 includes a battery case extending in the vertical direction, and Fig. 2 shows a laminated structure of the positive electrode, negative electrode, and separator when the lead-acid battery is viewed from above in the vertical direction (above the height direction of the battery case).

[0055] The lead-acid battery 100 shown in Figures 1 and 2 includes an electrode group 110, a battery case 120 that houses the electrode group 110, connecting members 130a, 130b connected to the electrode group 110, poles 140a, 140b connected to the connecting members 130a, 130b, a liquid inlet plug 150 that closes the liquid inlet of the battery case 120, and a support member 160 connected to the battery case 120.

[0056] The electrode group 110 includes a plurality of positive electrodes 10, a plurality of negative electrodes 20, and a plurality of separators 30. The positive electrodes 10 and the negative electrodes 20 are arranged alternately with the separators 30 interposed therebetween. An electrolyte solution 40 is filled in the space between the separators 30 around the positive electrodes 10.

[0057] The positive electrode 10 is, for example, a plate-shaped electrode (positive electrode plate) and includes a plurality of tubes (active material holding members) 10a for holding active material, a core metal (current collector) 10b, a positive electrode material 10c, a lower connecting seat 10d, an upper connecting seat 10e, and an ear portion 10f. The tube 10a of the positive electrode 10 is a cylindrical portion capable of housing the positive electrode material 10c containing the active material.

[0058] The multiple tubes 10a are arranged in parallel to one another to form a group of tubes 50 for holding active material. That is, the positive electrode 10 has a group of tubes 50 for holding active material. Each tube 10a extends in the height direction (vertical direction) of the battery case 120. The metal core 10b extends in the axial direction of the tube 10a at the center of the tube 10a. The positive electrode material 10c is filled between the tube 10a and the metal core 10b.

[0059] The lower linking seat 10d is connected to one end of the tube 10a (the lower end in the figure), and the upper linking seat 10e is connected to the other end of the tube 10a (the upper end in the figure). The lower linking seat 10d and the upper linking seat 10e are in contact with the tube 10a, the metal core 10b, and the positive electrode material 10c arranged in the tube 10a, and hold the tube 10a, the metal core 10b, and the positive electrode material 10c. The lower linking seat 10d is attached to the end of the tube 10a on the bottom side of the battery case 120 (the end of one end side of the tube 10a). The lower linking seat 10d is fitted to the end of the tube 10a, and has a base portion extending in a direction perpendicular to the axial direction of the tube 10a, and a plurality of fitting portions connected to the base portion and fitted to the end of the tube 10a. A recess is formed in the fitting portion into which the end of the metal core 10b is inserted. The upper link seat 10e is attached to the end of the tube 10a on the upper side of the battery case 120 (the other end of the tube 10a).

[0060] One end of the ear 10f (the lower end in the drawing) is connected to the upper connecting seat 10e, and the other end of the ear 10f (the upper end in the drawing) is connected to the connecting member 130a. The core metal 10b accommodated in the tube 10a is electrically connected to the pole 140a via the upper connecting seat 10e, the ear 10f, and the connecting member 130a.

[0061] The support member 160 has multiple protrusions 160a extending in the axial direction (longitudinal direction, for example, the height direction of the battery case 120) of the tube 10a, and the lower link seat 10d is fixed by contacting the multiple protrusions 160a. That is, the support member 160 supports the portion of the lower link seat 10d on the bottom side of the battery case 120 by the protrusions 160a.

[0062] The negative electrode 20 is, for example, in the form of a plate, for example, a paste-type negative electrode plate. The negative electrode 20 has a negative electrode current collector and a negative electrode material held by the negative electrode current collector. A plate-shaped current collector can be used as the negative electrode current collector. The negative electrode current collector and the core metal 10b of the positive electrode 10 may have the same composition or may be different from each other. The negative electrode 20 is electrically connected to the electrode pole 140b via a connecting member 130b.

[0063] The manufacturing method of the lead-acid battery according to the present embodiment includes an assembly process in which components including electrodes having active material holding members are assembled to obtain a lead-acid battery. In the assembly process, for example, an unformed positive electrode and an unformed negative electrode are stacked, and the current collectors of the electrodes of the same polarity are welded with a strap to obtain an electrode group. This electrode group is placed in a battery case to produce an unformed battery. The unformed positive electrode and the unformed negative electrode may be stacked with a separator interposed therebetween.

[0064] The manufacturing method of the lead acid battery according to the present embodiment may include an active material holding member fabrication step of fabricating an active material holding member using a resin member before the assembly step. The active material holding member fabrication step may include a molding step of forming a base material containing polyester into a cylindrical shape to obtain a cylindrical portion. The base material of the resin member in the active material holding member fabrication step may or may not hold a resin containing an epoxy resin and an acrylic resin. As a first aspect, in the molding step, the cylindrical portion may be formed by winding a resin sheet in a spiral or volute shape. As a second aspect, in the molding step, the cylindrical portion may be formed by joining resin sheets facing each other. As a third aspect, in the molding step, the resin sheet may be wound around the circumferential direction of the cylindrical portion with the pair of sides of the resin sheet facing each other facing each other facing each other, so that the pair of sides are oriented in the axial direction of the cylindrical portion, thereby forming the cylindrical portion. In the active material holding member fabrication step, after the molding step, a group of active material holding tubes may be obtained by arranging a plurality of cylindrical portions in a direction perpendicular to the axial direction of the cylindrical portion.

[0065] The manufacturing method of the lead acid battery according to the present embodiment may include a resin supporting step of supporting a resin containing an epoxy resin and an acrylic resin on a substrate before the assembly step and before or after the active material holding member fabrication step. In the resin supporting step, the substrate is impregnated with an emulsion in which the resin is dispersed in water, so that the resin can be supported on the substrate. After the substrate is impregnated with the emulsion, the substrate may be dried at 60 to 130° C. for 1 to 3 hours, for example.

[0066] The manufacturing method of the lead acid battery according to the present embodiment may include an electrode preparation step of preparing an electrode having an active material holding member. The electrode preparation step includes a positive electrode preparation step and a negative electrode preparation step. In the following, a case where the positive electrode has an active material holding member will be described.

[0067] In the positive electrode preparation step, a positive electrode is obtained that has a core inserted into an active material holding member (e.g., a cylindrical portion) and a positive electrode material filled between the active material holding member and the core. In the positive electrode preparation step, for example, after the core is placed in the cylindrical portion, raw materials for the positive electrode active material are filled between the core and the cylindrical portion, and the lower end of the cylindrical portion is sealed with a lower connecting seat to obtain a positive electrode that has an unformed positive electrode material. In the positive electrode preparation step, the upper end of the cylindrical portion may be sealed with an upper connecting seat.

[0068] In the negative electrode preparation process, for example, a negative electrode material paste containing raw materials for the negative electrode active material is filled into a negative electrode current collector (e.g., a current collector grid (cast grid, expanded grid, etc.)), and then aging and drying are performed to obtain a negative electrode having unformed negative electrode material.

[0069] The method for manufacturing a lead-acid battery according to this embodiment may include a chemical conversion process for performing chemical conversion on the positive and negative electrodes. The chemical conversion process may be performed after the assembly process, or may be performed in an electrode preparation process before the assembly process (tank chemical conversion). In the chemical conversion process, for example, chemical conversion is performed by passing a direct current through the positive and negative electrodes in contact with an electrolyte. A lead-acid battery can be obtained by adjusting the specific gravity of the electrolyte after chemical conversion to an appropriate specific gravity.

[0070] An electric vehicle (e.g., an electric vehicle) or a power supply device according to the present embodiment includes the lead acid battery according to the present embodiment. A manufacturing method for an electric vehicle or a power supply device according to the present embodiment includes a step of obtaining a lead acid battery by the manufacturing method for a lead acid battery according to the present embodiment. A manufacturing method for an electric vehicle or a power supply device according to the present embodiment includes, for example, a step of obtaining a lead acid battery by the manufacturing method for a lead acid battery according to the present embodiment, and a step of assembling components including the lead acid battery to obtain an electric vehicle or a power supply device. Examples of electric vehicles include a forklift and a golf cart. Examples of power supply devices include a UPS, a power supply for a disaster prevention (emergency) radio, a power supply for a telephone, and the like. According to the present embodiment, a lead acid battery for an electric vehicle (e.g., a lead acid battery for an electric vehicle) is provided, for example, a lead acid battery for a forklift is provided. According to the present embodiment, a lead acid battery for a power supply device is provided.

[0071] Lead-acid batteries for electric vehicles are likely to be designed with electrodes that are taller in the height direction of the battery. Therefore, sulfuric acid in the electrolyte is likely to settle downward, and the concentration of sulfuric acid in the region below the electrode increases due to stratification of the electrolyte, and the resin member below the active material holding member in the electrode is likely to deteriorate. In this case, if the mechanical strength of the resin member is reduced when it is contacted with sulfuric acid, the active material will leak significantly. On the other hand, the lead-acid battery according to this embodiment can suppress the reduction in the mechanical strength of the resin member when it is contacted with sulfuric acid, and therefore can suppress the leakage of the active material, and therefore can be suitably used in electric vehicles. EXAMPLES

[0072] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0073] <Preparation of resin sheet> Example 1 An emulsion containing acrylic resin (DIC Corporation, AJ-1800) and epoxy resin (DIC Corporation, EN-0270) is applied to a polyester nonwoven fabric (containing polyethylene terephthalate; average pore size: 38 μm, basis weight: 108 g / m 2) for 1 minute. Thereafter, it was dried in a thermostatic chamber at 100°C for 1 hour to obtain a resin sheet containing the resin held on the substrate. The total amount of the epoxy resin and acrylic resin held on the substrate was 15 mass% based on the total mass of the substrate, and the mass ratio of the epoxy resin and the acrylic resin was 20:80 (epoxy resin:acrylic resin).

[0074] Example 2 Except for changing the amounts of epoxy resin and acrylic resin used in the emulsion, a resin sheet was produced in the same manner as in Example 1. The total amount of epoxy resin and acrylic resin held on the substrate was 15 mass% based on the total mass of the substrate, and the mass ratio of epoxy resin to acrylic resin was 25:75 (epoxy resin:acrylic resin).

[0075] Example 3 Except for changing the amounts of epoxy resin and acrylic resin used in the emulsion, a resin sheet was produced in the same manner as in Example 1. The total amount of epoxy resin and acrylic resin held on the substrate was 15 mass% based on the total mass of the substrate, and the mass ratio of epoxy resin to acrylic resin was 30:70 (epoxy resin:acrylic resin).

[0076] Example 4 Except for changing the amounts of epoxy resin and acrylic resin used in the emulsion, a resin sheet was produced in the same manner as in Example 1. The total amount of epoxy resin and acrylic resin held on the substrate was 15 mass% based on the total mass of the substrate, and the mass ratio of epoxy resin to acrylic resin was 50:50 (epoxy resin:acrylic resin).

[0077] Comparative Example 1 A resin sheet was produced in the same manner as in Example 1, except that the emulsion was changed to use only acrylic resin without the epoxy resin. The amount of acrylic resin held on the substrate was 15 mass% based on the total mass of the substrate, and the mass ratio of epoxy resin to acrylic resin was 0:100 (epoxy resin:acrylic resin).

[0078] Comparative Example 2 Except for changing the amounts of epoxy resin and acrylic resin used in the emulsion, a resin sheet was produced in the same manner as in Example 1. The total amount of epoxy resin and acrylic resin held on the substrate was 15 mass% based on the total mass of the substrate, and the mass ratio of epoxy resin to acrylic resin was 75:25 (epoxy resin:acrylic resin).

[0079] Comparative Example 3 A resin sheet was produced in the same manner as in Example 1, except that the emulsion was changed to use only epoxy resin without using acrylic resin. The amount of epoxy resin held in the substrate was 15 mass% based on the total mass of the substrate, and the mass ratio of epoxy resin to acrylic resin was 100:0 (epoxy resin:acrylic resin).

[0080] <Thickness of resin sheet> The thickness of the resin sheet was measured at 10 points with a caliper, and the average value of the 10 points was taken as the thickness of the resin sheet. The results are shown in Table 1.

[0081] <Evaluation of pores> In the resin sheets of Examples 1 to 4, pores in the range of 0.006 to 0.1 μm as measured by mercury intrusion porosimetry accounted for less than 10% by volume of the total pore amount. In the resin sheets of Examples 1 to 4, the ratio A / B of the total pore volume A of pores with a pore diameter of 10 μm or more to the total pore volume B of pores with a pore diameter of less than 10 μm exceeded 1.40. The pore volume ratio of the resin sheet was calculated based on the pore distribution. The pore distribution of the resin sheet was measured using a pore distribution meter (manufactured by Shimadzu Corporation, product name: AUTO PORE IV 9520). The pore volume ratio of the resin sheet was calculated by separating the volume of each pore obtained from the measurement result of the pore distribution into "total pore volume of pores with a pore diameter of 10 μm or more" and "total pore volume of pores with a pore diameter of less than 10 μm" based on "total pore volume of pores with a pore diameter of 10 μm or more" / "total pore volume of pores with a pore diameter of less than 10 μm".

[0082] <Sulfuric acid degradation evaluation> Two sheets, Sheet A and Sheet B, were prepared as the above-mentioned resin sheets. Sheet B was placed in sulfuric acid with a specific gravity of 1.330 (20°C). After leaving it for 12 hours so that the sulfuric acid would penetrate into the sheet, the sheet was kept in a thermostatic chamber at 70°C and left there for 3 weeks. After that, the sheet was thoroughly washed with running water and then dried in a dryer at 60°C for 24 hours.

[0083] Test pieces measuring 20 mm x 70 mm were cut out from sheet A that had not been immersed in sulfuric acid, and from sheet B that had been immersed in sulfuric acid. The tensile strength of the test pieces in the CD direction of the nonwoven fabric was measured using an autograph (EZ-FX, manufactured by Shimadzu Corporation). The chuck distance was set to 20 mm, and the tensile speed was set to 5 mm / min. The strength retention rate [%] was measured using the following formula. The results are shown in Table 1. Strength retention rate = [(tensile strength of sheet B) / (tensile strength of sheet A)] x 100

[0084] <Electrical resistance measurement> A 70mm x 70mm x 1mm lead plate (3 or more types of plate as specified in JIS H 2105) was placed as a current electrode in the current electrode chamber of a test cell for electrical resistance described in SBA S0402. After placing a spacer to fix the test piece in place, sulfuric acid with a specific gravity of 1.280 (20°C) was poured to a height of 10mm from the upper edge of the test cell. After that, a mercury sulfate electrode with a saturated potassium sulfate aqueous solution as the internal solution was placed in the voltage electrode chamber, and the test cell was left to stand for 1 hour while maintaining the temperature at 25°C. Then, 1000mA was applied for 1 minute using an electrochemical measuring device (Hokuto Denko Corporation, HZ-5000), and the electrical resistance value R1 after 1 minute was obtained. Next, five test pieces measuring 70 mm x 70 mm were cut out from the resin sheet and immersed in sulfuric acid with a specific gravity of 1.280 (20°C) at 25°C for 24 hours. After that, one of the test pieces was inserted into the test piece insertion location while being fixed by sandwiching the test piece between spacers. At this time, the area of ​​the resistance measurement point on the test piece was 6 cm2. 2The above-mentioned electrochemical measuring device was used to pass a current of 1000 mA for 1 minute, and the electrical resistance value after 1 minute was obtained. This measurement was performed on the above-mentioned five test pieces, and the average value R2 of the five electrical resistance values ​​was obtained. Then, the electrical resistance value R (unit: mΩ / cm 2 The results are shown in Table 1. R = (R2-R1) / 6×1000

[0085] [Table 1] [Explanation of symbols]

[0086] 10...positive electrode (electrode), 20...negative electrode (electrode), 10a...tube (active material holding member), 100...lead-acid battery.

Claims

1. A resin member used in an active material holding member, A substrate including a polyester and a resin supported on the substrate, The resin includes an epoxy resin and an acrylic resin, A resin member, wherein the content of the epoxy resin is more than 0 mass % and 70 mass % or less based on the total amount of the epoxy resin and the acrylic resin.

2. The resin member according to claim 1 , wherein the content of the epoxy resin is more than 0 mass % and not more than 40 mass % based on the total amount of the epoxy resin and the acrylic resin.

3. The resin member according to claim 1 or 2, having a thickness of 0.05 to 1 mm.

4. The resin member according to any one of claims 1 to 3, wherein the total amount of the epoxy resin and the acrylic resin is 1 to 30 mass% based on the total mass of the base material.

5. An active material holding member comprising the resin member according to any one of claims 1 to 4.

6. a cylindrical portion including the resin member, the substrate comprises a nonwoven fabric, The active material holder according to claim 5 , wherein the MD and CD directions of the nonwoven fabric are inclined with respect to the axial direction of the cylindrical portion.

7. An electrode comprising the active material holding member according to claim 6 and an active material held by the active material holding member.

8. A positive electrode and a negative electrode are provided, A lead-acid battery, wherein at least one selected from the group consisting of the positive electrode and the negative electrode is the electrode according to claim 7.

9. 9. The lead acid battery of claim 8, further comprising a separator disposed between the positive electrode and the negative electrode.

10. An electric vehicle comprising the lead-acid battery according to claim 8 or 9.

Citation Information

Patent Citations

  • JP1970029539B1

  • Clad tube for battery and method of producing same

    JP1977156340A

  • Clad type lead-acid battery

    JP1996203506A

  • Separator for solid polymer type fuel cell and its method of manufacture

    JP2002164063A

  • Lithium secondary battery and method for manufacturing electrode thereof

    JP2011150819A